Modeling, stability and stick-slip behaviour analysis of coke pushing system. (August 2019) - Chen, Junjun; Sun, Huanwu; Gao, Hongbin; Fan, Yaoyao; Xu, Bing
Abstract: Coke pushing machine is a device for pushing coke out of an oven chamber of a coke oven. In the process of pushing coke, the pushing ram is in contact with the ground of the carbonization chamber through the slipper. The coke pushing process can be seen as a kind of sliding friction. In order to better research on the dynamic characteristics of the coke pushing system, a two-degree-of-freedom mechanical model is designed in this paper. Then we analyze the stability and stick-slip behaviour of the system by calculating the critical instability speed and the critical stick-slip speed of this system. To analyze the effects of different system parameters on the stability and stick-slip motion of the system, a detailed simulation analysis is carried out. Numerical simulation results of this paper are of benefit to the design and improvement of the coke pushing system. Highlights: A mechanical model is designed to research on the dynamic characteristics of coke pushing system. Calculating the critical instability speed and the critical stick-slip speed of this system. Investigate the effects of different system parameters on the stability and stick-slip motion..